2014
DOI: 10.1242/dev.111229
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis Mediator CDK8 module genes CCT (MED12) and GCT (MED13) are global regulators of developmental phase transitions

Abstract: Temporal coordination of developmental programs is necessary for normal ontogeny, but the mechanism by which this is accomplished is still poorly understood. We have previously shown that two components of the Mediator CDK8 module encoded by CENTER CITY (CCT; Arabidopsis MED12) and GRAND CENTRAL (GCT; Arabidopsis MED13) are required for timing of pattern formation during embryogenesis. A morphological, molecular and genomic analysis of the post-embryonic phenotype of gct and cct mutants demonstrated that these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 61 publications
1
34
0
Order By: Relevance
“…Taken together, these data suggest that somatic MED12 mutations may play a functional role in smooth muscle tumors. In accord with this notion, analysis of major cancer types including other types of sarcoma, as well as colon, breast, and lung carcinomas and gastrointestinal stromal tumor showed MED12 mutations exclusively in leiomyomas of the uterus (Je et al, 2012) (Bertsch et al, 2014) in smooth muscle tumors has been observed and general functional data regarding MED12 indicate a major role during developmental processes (Gillmor et al 2014;Wu et al, 2014) and in the modulation of sonic hedgehog (Zhou et al, 2006), TGFß signaling (Huang et al, 2012), and Wntsignaling Rocha et al, 2010); the latter being in line with the detection of MED12 mutations in colorectal cancer (Je et al, 2012;Forbes et al, 2014).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Taken together, these data suggest that somatic MED12 mutations may play a functional role in smooth muscle tumors. In accord with this notion, analysis of major cancer types including other types of sarcoma, as well as colon, breast, and lung carcinomas and gastrointestinal stromal tumor showed MED12 mutations exclusively in leiomyomas of the uterus (Je et al, 2012) (Bertsch et al, 2014) in smooth muscle tumors has been observed and general functional data regarding MED12 indicate a major role during developmental processes (Gillmor et al 2014;Wu et al, 2014) and in the modulation of sonic hedgehog (Zhou et al, 2006), TGFß signaling (Huang et al, 2012), and Wntsignaling Rocha et al, 2010); the latter being in line with the detection of MED12 mutations in colorectal cancer (Je et al, 2012;Forbes et al, 2014).…”
Section: Discussionmentioning
confidence: 73%
“…Corroborating these results, Kämpjärvi et al () detected MED12 mutations in exon 2 frequently in leiomyomas, only rarely in colorectal cancer and never in other hematological, mesenchymal and epithelial malignancies. Although the functional role of MED12 remains unclear, MED12 transcripts (Mäkinen et al, ) and expression of the protein (Bertsch et al, ) in smooth muscle tumors has been observed and general functional data regarding MED12 indicate a major role during developmental processes (Gillmor et al ; Wu et al, ) and in the modulation of sonic hedgehog (Zhou et al, ), TGF‐ß signaling (Huang et al, ), and Wnt‐signaling (Kim et al, ; Rocha et al, ); the latter being in line with the detection of MED12 mutations in colorectal cancer (Je et al, ; Forbes et al, ).…”
Section: Discussionmentioning
confidence: 95%
“…We find that despite the fact that M. nudatus is likely recently derived from a M. guttatus -like ancestor (Oneal et al ., 2014), these species exhibit different patterns of embryo and endosperm development. The temporal coordination of development across cell types with different developmental roles is increasingly recognized as a critical aspect of achieving normal development (Del Toro-De León et al ., 2014; Gillmor et al ., 2014). We suggest that divergence in the timing of development between M. guttatus and M. nudatus may partly underlie the near complete hybrid barrier between them.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, functional analyses demonstrate that two mediator (MED) subunits, MED12 and MED13, act as global regulators of developmental timing by fine-tuning the expression of temporal regulatory genes including miR156 [70]. In addition, genome-wide binding assays reveal that FUSCA3 (FUS3), a B3 domain transcription factor regulating seed development, and two MADS-box proteins, AGAMOUS-LIKE 15 (AGL15) and AGL18, are associated with regulatory regions of two miR156-coding loci [71,72].…”
Section: Future Directionsmentioning
confidence: 99%